PENGUATAN KEARIFAN LOKAL KEDIRI MELALUI CERITA PANJI DALAM PEMBELAJARAN MENULIS KREATIF BERBASIS AUGMENTED REALITY - Encil Puspitoningrum; Daniel Swanjaya; Rosa Imani Khan; Erina Ayu Lestari; Zakka Saputra (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyze the effectiveness of using Panji stories as a medium for strengthening local wisdom in Kediri in creative writing learning based on Augmented Reality (AR). Using a quantitative approach with a descriptive survey method, the study involved 250 junior high school students from 5 public junior high schools and 7 private junior high schools in Kediri City. Data were collected through a structured questionnaire consisting of 10 multiple-choice questions (a-d) that measured students' perceptions of the AR learning website, its impact on creative writing motivation, and their understanding of local wisdom. The results showed a very high level of student satisfaction with the AR learning website (mean 3.52-3.65), an increase in creative writing motivation in 67.2% of students, and an increase in understanding of local wisdom in 70.0% of students. AR technology has proven effective in bringing the Panji story to life as an immersive learning experience, increasing student engagement, and preserving local cultural heritage through educational technology innovations relevant to the digital generation.